Kolaborasi BUMDes dan Program CSR dalam Pemberdayaan Masyarakat: Studi pada Petani Kopi di Desa Baloi, Kabupaten Murung Raya - Novri Amdani Saragih; Saputra Adiwijaya; Ida Bagus Suryanatha (Journal of Economics and Social Sciences (JESS), 2026)
This study analyzes community empowerment through the collaboration between BUMDes Baloi Usaha Mandiri and the CSR program of PT Maruwai Coal in developing the coffee commodity “Kopi Baloi” in Tumbang Baloi Village, Murung Raya Regency. Using a qualitative case study guided by an integrated Asset-Based Community Development (ABCD), Creating Shared Value (CSV), and social capital framework, primary interview data were triangulated with the company’s social mapping report and development master plan (RIPPM). The findings show that the collaboration successfully mobilized five community assets into value-added products, including Kopi Baloi and “Baloi’s Signature” coffee-leaf tea. However, the study reveals a central paradox: strong bonding social capital and downstream production contrast with weak bridging social capital, caused by limited production scale, unstable quality standards, lack of business legality (SPP-IRT), and minimal digital-logistic access, leaving the marketing chain dominated by local middlemen. Theoretically, this shows that BUMDes-CSR synergy in mining-ring villages can mobilize assets without building the market-linking cluster CSV theory identifies as essential for shared value creation. Practically, the study recommends a three-pillar strategy: strengthening BUMDes governance and B2C marketing, CSR-facilitated B2B partnerships with a gradual exit strategy, and district government support for logistics infrastructure and licensing.